Analysis of Stress Characteristics and the Engineering Application of the Self-Balancing Retaining Wall. (11th September 2017) - Gan, Fei; Ye, XiaoMing; Yin, Ke; Li, Meilin; Bi, Jing
Abstract : A new type of retaining wall, the self-balance retaining wall, is introduced in this paper. Based on the stress analysis, the calculation model and method are advanced about the retaining wall. A comparative analysis related to traditional retaining wall is carried out on stress and cost combining with an actual project. The results show that the idea of using upper gravity retaining wall as the resistance of lower retaining wall is clever and reasonable that the self-balance retaining wall has a very wide scope of application relying on the anchor tensile conditions rarely and that the self-balance retaining wall has a great economic value with low cost. The cost of the self-balance retaining wall is 50% compared with the cantilever pile retaining wall under the same conditions which has a good economic effect and application prospect.